Increased serum ferritin levels are independently associated with carotid atherosclerosis in women. Issue 11 (19th July 2017) - Xu, Haiyan; Song, Yanqi; Xu, Jing; Gu, Yeqing; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Xia, Yang; Bao, Xue; Shi, Hongbin; Su, Qian; et al.
Abstract: Previous studies have supported the theory that there is a positive association between ferritin and carotid atherosclerosis in Western people. Diet plays an important role in determining serum ferritin concentration. Asian dietary patterns are different from Western dietary patterns, implying that there may be a difference in the association of ferritin with carotid atherosclerosis between Asian and Western people. However, few studies focus on the association between ferritin and carotid atherosclerosis among Asians. The aim of this study was to investigate how serum ferritin levels are associated with carotid atherosclerosis in an Asian adult population. A cross-sectional assessment was performed in 8302 adults in Tianjin, China. Carotid intima-media thickness (IMT) and plaques were assessed using ultrasonography, and serum ferritin was measured using the protein chip-chemiluminescence method. Multiple logistic regression analysis was used to examine the association between quartiles of serum ferritin concentration and carotid atherosclerosis. In the present study, the overall prevalence of IMT and carotid plaques in participants is 29·2 and 22·7 %, respectively. In women, after adjustments for potentially confounding factors, the OR of IMT and carotid plaques by increasing serum ferritin quartiles were 1·00, 1·39 (95 % CI 0·98–1·99), 1·39 (95 % CI 0·99–1·97), 1·81 (95 % CI 1·30–2·55) ( P for trend <0·001) and 1·00, 1·24 (95 % CI 0·89–1·73), 1·18 (95 % CI 0·85–1·65), 1·59 (95 % CI 1·15–2·20) ( P for trend <0·01), respectively. However, no association was found between serum ferritin and carotid atherosclerosis in men. The study demonstrated that increased serum ferritin levels are independently associated with IMT and carotid plaques in Asian women but not in Asian men.